KONFLIK TOKOH UTAMA DALAM NOVEL ANKOKU JOSHI KARYA AKIYOSHI RIKAKO - Risvy, Intan; Anwar, Fithyani; El Risman, Yunita (Universitas Hasanuddin, 2024)
In this research, the writer wants to examine the conflict of Shiraishi Itsumi's character in Ankoku Joshi. To analyze this, a structural approach is used with a qualitative descriptive research method. The purpose of this research is to analyze the conflict of Shiraishi Itsumi's character in Akiyoshi Rikako's Ankoku Joshi novel. The data used in this research is the novel Ankoku Joshi by Akiyoshi Rikako which is paired with the Indonesian translation of the novel which was published in 2014. The results of the study show that Shiraishi Itsumi's character experiences external conflict because she is arrogant and want to be the most shining compared to other figures. The internal conflict is also experienced by the character Shiraishi Itsumi due to the influence of her social background which makes her arrogant. The conflict relationship with the background influences each other because the character's character is influenced by the background.